Teacher attunement to preschool children's peer preferences: Associations with child and classroom-level variables - Peceguina, Maria Inês Duarte (2022)
Teacher attunement to peer preferences in preschool was assessed as the level of teacher-child agreement on each child’s preferred playmates. The associations between attunement and children’s age, sex, disability status (with or without disabilities), time spent with teacher, and classroom level variables - group size, emotional support, classroom organization, instructional support, and teacher experience - were investigated. Participants were 1415 children from 86 classrooms (743 boys and 672 girls; Mage = 62.15 months, SD = 8.80), including 108 children with disabilities. Overall, results showed that higher teacher attunement was associated with children’s age (being older) and not having a disability. Implications for educational policies and classroom-level professional development are discussed.